2012
DOI: 10.1038/cr.2012.160
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional activation of transposable elements in mouse zygotes is independent of Tet3-mediated 5-methylcytosine oxidation

Abstract: The methylation state of the paternal genome is rapidly reprogrammed shortly after fertilization. Recent studies have revealed that loss of 5-methylcytosine (5mC) in zygotes correlates with appearance of 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC). This process is mediated by Tet3 and the 5mC oxidation products generated in zygotes are gradually lost during preimplantation development through a replicationdependent dilution process. Despite these findings, the biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 45 publications
8
40
2
Order By: Relevance
“…Immunostaining with an antibody against the C-terminus of Tet3 protein (Gu et al, 2011) confirmed lack of Tet3 protein in the CKO zygotes (Figure 1A). Similar to previous reports (Gu et al, 2011; Inoue et al, 2012), Tet3 is predominantly localized in the paternal pronucleus. Interestingly, weaker but detectable Tet3 staining signals were also observed in the maternal pronucleus, and this signal was absent in CKO zygotes (Figure 1A).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Immunostaining with an antibody against the C-terminus of Tet3 protein (Gu et al, 2011) confirmed lack of Tet3 protein in the CKO zygotes (Figure 1A). Similar to previous reports (Gu et al, 2011; Inoue et al, 2012), Tet3 is predominantly localized in the paternal pronucleus. Interestingly, weaker but detectable Tet3 staining signals were also observed in the maternal pronucleus, and this signal was absent in CKO zygotes (Figure 1A).…”
Section: Resultssupporting
confidence: 91%
“…This loss of 5mC is explained by rapid conversion of 5mC to 5hmC and its further oxidation products catalyzed by the maternally stored Tet3 proteins (Gu et al, 2011; Inoue et al, 2012; Wossidlo et al, 2011). Immunostaining studies indicated that 5mC derived oxidation products are gradually lost during preimplantation development through a DNA replication-dependent manner (Inoue et al, 2011; Inoue and Zhang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…3). Furthermore, removal of Tet3, which takes part in the active demethylation of DNA in zygotes via oxidation of 5mC to 5hmC, does not lead to changes in L1 transcription (Inoue et al 2012). Thus, the temporal pattern of L1 transcriptional activation and subsequent silencing cannot be explained through changes in DNA methylation or in H3K9me3 after fertilization and prior to implantation, implying that additional pathways are involved in the process.…”
Section: Regulation Of L1 Expressionmentioning
confidence: 95%
“…This suggests that Tet3 protein retained in the recipient cytoplasm is not sufficient to trigger massive 5mC oxidation in the reconstructed embryos. This is plausible because Tet3 mainly localizes to the paternal pronuclei that have been removed from the recipients (Gu et al, 2011;Inoue et al, 2012). Additionally, since Tet3 is no longer localized to nuclei after the first mitosis (Gu et al, 2011), the time window during which the remaining Tet3 can function is very limited due to the quick entry of the embryo into the first mitosis (within 2 hr after fusion).…”
Section: Tet3-mediated Paternal 5mc Oxidation Is Dispensable For Mousmentioning
confidence: 97%